AGE CHARACTERISTICS OF THE PERSONALITY OF JUVENILES AS THE GROUNDS FOR EXEMPTION FROM CRIMINAL PUNISHMENT - V. A. Terentieva; I. V. Masalitina (Вестник Кемеровского государственного университета, 2015)
The paper is devoted to one of the topical issues of exemption from criminal penalties – the age peculiarities of the personality of juveniles. The authors analyzed the age-specific features based on the methods of investigation, as well as taking into account the influence of the measures of criminal law. Analyzing the age features of juveniles, it should be noted that commitment of wrongful acts is determined by such age peculiarities of teenagers as the tendency to imitate, exposure to outside influences, contradictory views and erratic behavior, increased emotional excitability